2016
DOI: 10.1177/2325967116675822
|View full text |Cite
|
Sign up to set email alerts
|

Return to Play and Prior Performance in Major League Baseball Pitchers After Repair of Superior Labral Anterior-Posterior Tears

Abstract: Background:The published return-to-play (RTP) rates for Major League Baseball (MLB) pitchers who have undergone surgical repair of superior labrum anterior-posterior (SLAP) tears vary widely and are generally accepted to be lower in the subset of competitive throwers. The efficacy of surgical treatment for MLB players is largely unknown.Purpose:To examine the RTP rate and performance of MLB pitchers who have undergone SLAP tear repair between 2003 and 2010.Study Design:Descriptive epidemiological study.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 14 publications
2
43
1
1
Order By: Relevance
“…Unfortunately, this study only adds to the existing literature highlighting poor rates of return to sport for throwing athletes after SLAP repair. Even in the most expert of hands, published rates of a successful return to the preinjury level of performance range from 38% to 60%, [2][3][4] with a rate as low as 10% for pitchers. 5 For throwing and nonthrowing athletes alike, the posterior extension of these injuries would logically entail a more extensive and posteriorly based repair (and subsequent rehabilitation) than in typical type II injuries.…”
Section: See Related Article On Page 3159mentioning
confidence: 99%
“…Unfortunately, this study only adds to the existing literature highlighting poor rates of return to sport for throwing athletes after SLAP repair. Even in the most expert of hands, published rates of a successful return to the preinjury level of performance range from 38% to 60%, [2][3][4] with a rate as low as 10% for pitchers. 5 For throwing and nonthrowing athletes alike, the posterior extension of these injuries would logically entail a more extensive and posteriorly based repair (and subsequent rehabilitation) than in typical type II injuries.…”
Section: See Related Article On Page 3159mentioning
confidence: 99%
“…Baseball players, specifically pitchers, are susceptible to SLAP tears and have the lowest return to sport outcomes [ 58 ]. While overall shoulder scores improve with surgical treatment of Type II SLAP tears, the return to play outcome is significantly lower then other athletic populations [ 44 , 59 ]. Smith et al [ 59 ] found that only 62.5% of Major League Baseball pitchers were able to return to the major league level, and only 54% returned to their previous level of performance.…”
Section: Introductionmentioning
confidence: 99%
“…While overall shoulder scores improve with surgical treatment of Type II SLAP tears, the return to play outcome is significantly lower then other athletic populations [ 44 , 59 ]. Smith et al [ 59 ] found that only 62.5% of Major League Baseball pitchers were able to return to the major league level, and only 54% returned to their previous level of performance. This is still an improvement compared to non-operative outcomes report by Fedoriw et al [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…24 Previous studies reporting outcomes in patients undergoing repair for type II SLAP lesions have demonstrated inconsistent return to activity and functional scores, especially in overhead athletes. 5,7,19,24,27,37 While knotted anchors have traditionally been utilized during arthroscopic repair, 18,30 concerns over knot migration and knot abrasion within the shoulder have led to an increased interest in the use of knotless anchors over the past decade. 2,3,13,31,32,40 However, no investigation has examined postoperative outcomes based on differences in implant type in patients undergoing arthroscopic management of isolated type II SLAP lesions using suture anchors.…”
mentioning
confidence: 99%